Primary biliary cholangitis: perception and expectation of illness. Issue 9 (September 2022) - Floreani, Annarosa; Scaffidi, Michela; Coco, Barbara; Giannini, Edoardo Giovanni; Labanca, Sara; Bonaiuto, Emanuela; De Martin, Sara; Invernizzi, Pietro; Carbone, Marco; Alvaro, Domenico; Bragazzi, Maria Consiglia; Calvaruso, Vincenza; et al.
Abstract: An important tool to explore personal experience of symptoms, treatment and clinical outcome is stratification of illness perception in patients affected by PBC. Aim: To assess the perception of illness in a cohort of Italian patients with PBC. Methods: Between June and December 2019, a specific questionnaire was administered to a pool of 210 patients from 7 tertiary Italian centers, in order to identify and assess the patient's past history, symptoms and their impact on the quality of life, follow-up, treatment and perceived satisfaction of patients toward the provided care. Results: Fatigue, pruritus, and abdominal discomfort and sicca syndrome were present in 50.4%, 45%, 30.4% and 28.5% of patients, fatigue having the most impacting the daily-life. After a consultation with a specialist, the diagnosis of PBC was met within 18 months for 143 patients. Patients were mostly concerned about possible health problems that occur and in 25% of cases, symptoms had a negative impact on their life. Eighty percent of patients said they were satisfied with efficacy and tolerability of treatment, while 26% requested an improvement in the relationship with the specialist. Conclusions: The results highlight the importance of both promoting timely referral to the specialist and facilitating communication between healthcare professionals and patients.